"She was certainly not a Rosa Luxemborg" : a biography of Cissie Gool in images and words - Paleker, Gairoonisa (Department of Historical Studies, 2014)
Accompanied by a DVD entitled: Cissie Gool.|Bibliography: leaves 58-63.